2014
DOI: 10.1111/ped.12213
|View full text |Cite
|
Sign up to set email alerts
|

Two children with obesity‐related glomerulopathy identified in a school urinary screening program

Abstract: The incidence of obesity-related glomerulopathy (ORG) has increased over the last decade, but there have been few reports on ORG in Japanese children. Reported herein are two children with ORG identified on school urinary screening (SUS). Patient 1 was a 12-year-old boy in whom proteinuria was first detected on SUS. His body mass index (BMI) was 33.8 kg/m(2) and he had hypertension and hyperuricemia. Patient 2, a 10-year-old boy, also had proteinuria identified on SUS. His BMI was 34.8 kg/m(2) , and he had fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Limited clinic case reports showed that proteinuria was usually first detected and common in child ORG patients with or without hematuria, hyperuricemia, hypertension, and dyslipidemia. Renal biopsies of ORG patients have demonstrated glomeruli hypertrophy, proliferation of mesangial cells, and mesangial matrix expansion with or without segmental sclerosis ; these histologic changes are similar with what we observed in the present study. Meta‐analysis has shown that obesity could be associated with the development of renal dysfunction in childhood .…”
Section: Discussionsupporting
confidence: 91%
“…Limited clinic case reports showed that proteinuria was usually first detected and common in child ORG patients with or without hematuria, hyperuricemia, hypertension, and dyslipidemia. Renal biopsies of ORG patients have demonstrated glomeruli hypertrophy, proliferation of mesangial cells, and mesangial matrix expansion with or without segmental sclerosis ; these histologic changes are similar with what we observed in the present study. Meta‐analysis has shown that obesity could be associated with the development of renal dysfunction in childhood .…”
Section: Discussionsupporting
confidence: 91%
“…Microalbuminuria has been shown to be a sensitive marker of early-stage damage to the glomeruli, and it increases as kidney disease worsens. 21 This study demonstrated that the urine albumin in the obesity-related nephropathy group was higher than that in the control group, was positively correlated with the RI, and increased as microproteinuria increased. Therefore, the RI can indirectly reflect early-stage glomerular damage.…”
Section: Discussionmentioning
confidence: 61%
“…This lack of a difference might have been because the time since diagnosis was relatively short in all selected cases. Microalbuminuria has been shown to be a sensitive marker of early‐stage damage to the glomeruli, and it increases as kidney disease worsens . This study demonstrated that the urine albumin in the obesity‐related nephropathy group was higher than that in the control group, was positively correlated with the RI, and increased as microproteinuria increased.…”
Section: Discussionmentioning
confidence: 63%
“…ORG often occurs in young to middle-aged adults, with a male predominance; however, it can occur in all age groups, including children and elderly individuals. 17,23,24 The frequent background comorbidities of ORG patients include hypertension and dyslipidemia. 6−11 In general, the initial obesity-associated kidney phenotype is characterized as isolated proteinuria (without hematuria) with or without a GFR decrease.…”
Section: Clinical Features Of Orgmentioning
confidence: 99%